Leucyl-tRNA Synthetase Regulates Lactation and Cell Proliferation via mTOR Signaling in Dairy Cow Mammary Epithelial Cells - Wang, Lina; Lin, Ye; Bian, Yanjie; Liu, Lili; Shao, Li; Lin, Lin; Qu, Bo; Zhao, Feng; Gao, Xuejun; Li, Qingzhang (International journal of molecular sciences, 2014)
The role of LeuRS, an aminoacyl-tRNA synthetase, as an intracellular l-leucine sensor for the mTORC1 pathway has been the subject of much research recently. Despite this, the association between LeuRS and lactation in dairy cow mammary epithelial cells (DCMECs) remains unknown. In this study, we found that LeuRS expression in mammary gland tissue was significantly higher during lactation than pregnancy. Moreover, our data demonstrates that LeuRS is localized in the cytoplasm. Treatment with leucine increased DCMECs viability and proliferation, as well as mammalian target of rapamycin (mTOR), p-mTOR, ribosomal protein S6 kinase 1 (S6K1), p-S6K1, β-Casein, sterol regulatory element binding protein 1c (SREBP-1c), glucose transporter 1 (GLUT1), and Cyclin D1 mRNA and protein expression. Secretion of lactose and triglyceride were also increased. siRNA-mediated knockdown of LeuRS led to reduction in all of these processes. Based on these data, LeuRS up-regulates the mTOR pathway to promote proliferation and lactation of DCMECs in response to changes in the intracellular leucine concentration.